2002
DOI: 10.1023/a:1015207428675
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memory specificity, intrusive memory, and general memory skills in Dutch–Indonesian survivors of the World War II Era

Abstract: A lack of specific autobiographical memory may result from exposure to psychological trauma, intrusive memories of adverse events, and/or a general memory deficit. This study explored the role of these variables in 25 patients with various psychiatric diagnoses and 15 healthy controls. All participants had been exposed to war atrocities during their childhood in Indonesia. Patients produced significantly less specific memories than did controls. In addition, rather than performance on general neuropsychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
80
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 28 publications
11
80
1
3
Order By: Relevance
“…Subsequent studies have extended these findings, demonstrating an association between exposure to trauma and overgeneral autobiographical memory retrieval (Dalgleish et al, 2003;de Decker, Hermans, Raes, & Eelen, 2003;Hermans et al, 2004;Wessel, Merckelbach, & Dekkers, 2002). Furthermore, an association has been observed between overgeneral autobiographical memory and posttraumatic stress disorder (PTSD; e.g., McNally, Lasko, Macklin, & Pitman, 1995), acute stress disorder (Harvey, Bryant & Dang, 1998), and major depressive disorder (MDD; e.g., Kuyken & Brewin, 1995;Moore, Watts, & Williams, 1988).…”
mentioning
confidence: 90%
“…Subsequent studies have extended these findings, demonstrating an association between exposure to trauma and overgeneral autobiographical memory retrieval (Dalgleish et al, 2003;de Decker, Hermans, Raes, & Eelen, 2003;Hermans et al, 2004;Wessel, Merckelbach, & Dekkers, 2002). Furthermore, an association has been observed between overgeneral autobiographical memory and posttraumatic stress disorder (PTSD; e.g., McNally, Lasko, Macklin, & Pitman, 1995), acute stress disorder (Harvey, Bryant & Dang, 1998), and major depressive disorder (MDD; e.g., Kuyken & Brewin, 1995;Moore, Watts, & Williams, 1988).…”
mentioning
confidence: 90%
“…Furthermore, several studies have shown that reduced memory specificity is significantly associated with avoidance of intrusive thoughts [e.g. Kuyken and Brewin, 1995;Stokes et al, 2004;Wessel et al, 2002]. Raes et al [2006b] showed that this association even remains when controlling for level of depression and working memory capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive models of PTSD suggest that our overgeneral memory for traumatic events may limit ability of the patient to integrate the traumatic memories with other autobiographical memory and one's self-concept (Dalgleish, 2004). And intrusions of memories in a long period of time absorb the resources that could be used for effortful memory research (Wessel, Merckelbach, & Dekkers, 2002). Williams (1996) proposed that overgeneral memory helps patients block emotional events with negative effects (Geraerts, Dritschel, Kreplin, Miyagawa, & Waddington 2012).…”
Section: Discussionmentioning
confidence: 99%